Serum proteomics in giant cell arteritis in response to a three-day pulse of glucocorticoid followed by tocilizumab monotherapy (the GUSTO trial) - Christ, Lisa; Gloor, Andrea D.; Kollert, Florian; Gaber, Timo; Buttgereit, Frank; Reichenbach, Stephan; Villiger, Peter M. (Frontiers in Immunology, 2023)
Objective: Proteome analyses in patients with newly diagnosed, untreated giant cell arteritis (GCA) have not been reported previously, nor are changes of protein expression upon treatment with glucocorticoids (GC) and/or tocilizumab (TCZ) known. The GUSTO trial allows to address these questions, provides the opportunity to learn about the differential effects of GC and TCZ on proteomics and may help to identify serum proteins to monitor disease activity. Methods: Serum samples obtained from 16 patients with new-onset GCA at different time points (day 0, 3, 10, and week 4, 24, 52) during the GUSTO trial (NCT03745586) were examined for 1436 differentially expressed proteins (DEPs) based on proximity extension assay technology. The patients received 500 mg methylprednisolone intravenously for 3 consecutive days followed by TCZ monotherapy. Results: When comparing day 0 (before the first GC infusion) with week 52 (lasting remission), 434 DEPs (213↑, 221↓) were identified. In response to treatment, the majority of changes occurred within 10 days. GC inversely regulated 25 proteins compared to remission. No difference was observed between weeks 24 and 52 during established remission and ongoing TCZ treatment. Expression of CCL7, MMP12, and CXCL9 was not regulated by IL6. Conclusion: Disease-regulated serum proteins improved within 10 days and were normalized within 24 weeks, showing a kinetic corresponding to the gradual achievement of clinical remission. The proteins inversely regulated by GC and TCZ shed light on the differential effects of the two drugs. CCL7, CXCL9, and MMP12 are biomarkers that reflect disease activity despite normalized C-reactive protein levels.